Methods for social theory : analytical tools for theorizing and writing - Karlsson, Jan (Routledge, 2017)
This book constitutes a practical guide to the important skills of both theorizing and writing in social scientific scholarship, focusing on the importance of identifying relations between concepts that are useful for explaining social entities and of producing a text that convincingly advances the theory that has been constructed. Taking as its point of departure the distinction between the research process and the reporting process – between clarifying one’s ideas to oneself and writing to express these ideas clearly to others – this volume concentrates on writing when theorizing as a way of thinking, emphasizing the series of relations that exist between ontology, epistemology and rhetoric upon which successful theoretical writing depends.